MANAGEMENT OF COMMON POISONING: CHANGING TRENDS & CHALLENGES (Indian Internet Journal of Forensic Medicine and Toxicology, 2005)
Knowledge of poisons, their clinical manifestations, remedial measures, etc. and the causing of death by poisoning, was prevalent  in India since time immemorial. The ability to diagnose and manage a case of poisoning (clinical toxicology), identification of the  poison on analysis of the body fluids and the samples (analytical toxicology) and understanding the legal aspects of acute and  chronic poisoning may have changed with the passage of time. The recent past has witnessed important advances that aid both in  the diagnosis and the treatment of poisoned patient, however, the general principles of management including what to do, in what  order to do and why to institute a certain procedure, remain unchanged. This paper examines and discusses epidemiology,    actions, diagnosis and management of common poisoning cases reporting to the health care systems particularly in the Northern   India.
Keywords: tremendous; phenomenon; POISON